DEVELOPMENT AND VALIDATION OF A RP-HPLC METHOD FOR DETERMINATION OF ERDAFITINIB IN MARKETED FORMULATIONS - M. Maithani; D. Dwivedi; Hatwal, D.; P. Bansal (Journal of Biomedical and Pharmaceutical Research, 2020)
A simple and precise RP-HPLC method for the estimation of Erdafitinib in tablet dosage form was developed and validated. The chromatographic separation of the drug was done with a Hypersil™ ODS C18 Column (150 mm × 4.6 mm i.d., particle size 5 μ) using 20mM sodium acetate buffer (pH 4. ±0.02), methanol and acetonitrile (60:10:30 v/v/v) as a mobile phase. The instrument was set at flow rate of 1.0 mLmin-1 at ambient temperature and the wavelength of UV-visible detector at 310nm. The method showed excellent linearity over a range of 5-35 μgmL-1 for the drug. The correlation coefficient for Erdafitinib was noted to be 0.9999. The mean recovery values were found to be 99.77% and 100.88%. The results suggest that the proposed method could be suitable for quantitative determination of Erdafitinib in pharmaceutical preparations and also for quality control in bulk manufacturing. The F-test and t-test at 95% confidence level were applied on data for statistical analysis.